Fabrication of flexible chitosan film reinforced with pulping by-product lignosulfonates for cherry-tomato preservation - Zhu, Jiangyu; Fang, Yujie; Wakisaka, Minato; Saadiah Hafid, Halimatun; Yang, Zhengfei; Yin, Yongqi; Omura, Taku; Fang, Weiming (Elsevier BV, 2024)
The massive production of food waste and plastic pollution necessitates innovative solutions. This study reports the first fabrication of a flexible chitosan (CH) film reinforced with lignosulfonate (LS) derived from pulping byproduct as a sustainable alternative to synthetic food packaging. The CH/LS composite film was prepared by a simple casting method with varying LS contents of 1 % and 2 %. Compared to CH film, the addition of 2 % LS increased the tensile strength by over 4 times and decreased water vapor permeability by 11 %. Moreover, the CH/LS film exhibited excellent UV-shielding properties. This novel use of LS to reinforce CH film presents an eco-friendly active packaging material. When used to package cherry tomatoes for 2 weeks, the CH/LS film effectively maintained fruit freshness and hardness while minimizing weight loss. This work provides new scientific evidence on the optimized preparation and application of CH/LS composite films from renewable resources for food preservation.